International terrorism and features of the fight against it at the regional level on the ex ample of the EU and the SCO - Iarmosh, Olena; Khomiakova, Maryna (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article considers the characteristics of international terrorism as a phenomenon that requires joint efforts at the regional and supranational levels in political, social, economic, legal, ideological and other aspects, its causes and consequences, approaches to classification. Particular attention is paid to the analysis of existing problems of international regional security caused by terrorism, as well as the features of combating it on the example of the EU and the SCO. Scientific, official, historical sources of information were used in the research. The subject is the components of the strategy to combat international terrorism on the example of two regional international organizations, the EU and the SCO. The goal of the article is to determine the features and priorities of the fight against international terrorism at the regional level, their effectiveness and shortcomings on the basis of a comprehensive study of the features of the phenomenon. The objective is to analyze official sources on methods of combating international terrorism on the example of the EU and the SCO, to determine the causes, consequences and priorities for fighting against it. Research methods are comparative analysis, systematization and generalization. The following results were obtained: the main problem of combating international terrorism and its consequences at the regional level was identified, which is primarily related to the uniform content of agreements, statements, decisions, etc., without taking into account the region specifics. In addition, the priority areas of activity of international organizations that need attention have been identified, among them: prevention and cessation of terrorist financing, counteraction to the use of the Internet for terrorist purposes, promotion of cooperation in the fight against terrorism, etc. The conclusions of this work indicate the low efficiency of the organizations and the need to improve the tools of combating international terrorism on the basis of the general problems and priorities mentioned in the article.